2015
DOI: 10.3390/ijerph120100402
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia and Statins Affect Neurological Outcome in Lumbar Spine Injury

Abstract: The disabling pathophysiologic effects of lipid and neuroprotective effects of statins have recently been demonstrated for acute spinal cord injuries in animal models. This large scale population-based study aimed to investigate the effect hyperlipidemia and the use of statins in patients with lumbar spine injury. The National Health Insurance Research Database of Taiwan was used to identify patients with lumbar spine injury. A total of 2844 patients were grouped into three: no hyperlipidemia, hyperlipidemia u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Furthermore, spinal cord of offspring of atorvastatin showed a moderate degree of amelioration, except a slight accumulation of heterochromatin within neuronal cells. Similar findings were reported by Chung et al [20] in patients with disability of the lumbar spinal cord and received low dose statin drug treatment. Also, the observed damage demyelination and neuronal cell death reflected by upregulation of 8-doxyhydroxyguanosine, caspase 3, caspase 7 and increase of single strand DNA damage in neonates of hypercholesterolemic mother.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, spinal cord of offspring of atorvastatin showed a moderate degree of amelioration, except a slight accumulation of heterochromatin within neuronal cells. Similar findings were reported by Chung et al [20] in patients with disability of the lumbar spinal cord and received low dose statin drug treatment. Also, the observed damage demyelination and neuronal cell death reflected by upregulation of 8-doxyhydroxyguanosine, caspase 3, caspase 7 and increase of single strand DNA damage in neonates of hypercholesterolemic mother.…”
Section: Discussionsupporting
confidence: 90%
“…Experimental rats subjected for atorvastatin-treatment (10 mg/kg b. wt, OA) revealed improvement of brain cholesterol synthesis [17], decrease apoptosis and improve and locomotion after spinal cord injury [18,19]. Hyperlipidemic patients possessed a neurological disability of the lumbar spinal cord and improved only after low dose statin drug treatment [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study found the cucumber has a greater impact on hyperlipidemia. One glass of cucumber juice (125 ml) for the period of 4 months was statistically (P< 0.05) significant in decreasing the TC, LDL and TG experimental group 10 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the previous studies evaluated the nano particles of almond in hyperlipidemia in human. Supplementation of 2 g of almond nano paste (almonds were fabricated into nano particles and also grounded to form almond paste) for a period of two months brought reduction in lipid profile of hyperlipidemic subjects [10][11] . In a non pharmacological study, participants were given flaxseed powder 15 g and 20 g for two groups respectively for 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…reported that hyperlipidemia adversely affects the recovery of neurological function in patients with SCI. Therefore, theoretically, statins may reverse neurological disability in patients with SCI ( 121 ). However, in 2017, the only clinical trial investigating the efficacy of atorvastatin in patients with acute SCI found no significant improvement at the 3- and 6-month follow-up in patients receiving the drug ( 122 ).…”
Section: Potential Pharmaceutical Immunotherapeutic Drugs For Spinal ...mentioning
confidence: 99%